Advanced spreadsheet & database - iBook Development Group (Philippines : iBook Publishing, 2015)
"The book's primary focus is on teaching data analysis and develops problem solving skills in order to create effective spreadsheets and workbook files and database applications, with a secondary focus on teaching how to use tools in Microsoft Office Excel and Access 2010. In other words, the purpose of the book is to teach students how to provide effective and efficient information using a spreadsheet and database program."
Includes biblioraphy.
English text.
Keywords: Microsoft Excel (Computer software).; Database design